Enhanced skeletal muscle regrowth and remodelling in massaged and contralateral non‐massaged hindlimb. (1st December 2017) - Miller, Benjamin F.; Hamilton, Karyn L.; Majeed, Zana R.; Abshire, Sarah M.; Confides, Amy L.; Hayek, Amanda M.; Hunt, Emily R.; Shipman, Patrick; Peelor, Frederick F.; Butterfield, Timothy A.; Dupont‐Versteegden, Esther E.
Abstract : Key points: Muscle fibre cross sectional area is enhanced with massage in the form of cyclic compressive loading during regrowth after atrophy. Massage enhances protein synthesis of the myofibrillar and cytosolic, but not the mitochondrial fraction, in muscle during regrowth. Focal adhesion kinase activation and satellite cell number are elevated in muscles undergoing massage during regrowth. Muscle fibre cross sectional area and protein synthesis of the myofibrillar fraction, but not DNA synthesis, are elevated in muscle of the contralateral non‐massaged limb. Massage in the form of cyclic compressive loading is a potential anabolic intervention during muscle regrowth after atrophy. Abstract: Massage, in the form of cyclic compressive loading (CCL), is associated with multiple health benefits, but its potential anabolic effect on atrophied muscle has not been investigated. We hypothesized that the mechanical activity associated with CCL induces an anabolic effect in skeletal muscle undergoing regrowth after a period of atrophy. Fischer–Brown Norway rats at 10 months of age were hindlimb unloaded for a period of 2 weeks. The rats were then allowed reambulation with CCL applied at a 4.5 N load at 0.5 Hz frequency for 30 min every other day for four bouts during a regrowth period of 8 days. Muscle fibre cross sectional area was enhanced by 18% with massage during regrowth compared to reloading alone, and this was accompanied by elevated myofibrillar and cytosolic protein as well as DNA synthesis. Focal adhesion kinase phosphorylation indicated that CCL increased mechanical stimulation, while a higher number of Pax7 + cells likely explains the elevated DNA synthesis. Surprisingly, the contralateral non‐massaged limb exhibited a comparable 17% higher muscle fibre size compared to reloading alone, and myofibrillar protein synthesis, but not DNA synthesis, was also elevated. We conclude that massage in the form of CCL induces an anabolic response in muscles regrowing after an atrophy‐inducing event. We suggest that massage can be used as an intervention to aid in the regrowth of muscle lost during immobilization. Key points: Muscle fibre cross sectional area is enhanced with massage in the form of cyclic compressive loading during regrowth after atrophy. Massage enhances protein synthesis of the myofibrillar and cytosolic, but not the mitochondrial fraction, in muscle during regrowth. Focal adhesion kinase activation and satellite cell number are elevated in muscles undergoing massage during regrowth. Muscle fibre cross sectional area and protein synthesis of the myofibrillar fraction, but not DNA synthesis, are elevated in muscle of the contralateral non‐massaged limb. Massage in the form of cyclic compressive loading is a potential anabolic intervention during muscle regrowth after atrophy.